Settlement of Criminal Cases through Peace Agreements from the Perspective of Restorative Justice in Indonesia: Challenges and Legal Implications - Abdurrachman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was. This study aims to examine the settlement of criminal cases through peace-based mechanisms within the framework of restorative justice, with particular emphasis on the challenges of implementation and the resulting legal implications in the practice of law enforcement in Indonesia. Materials and methods. This research employs a normative legal research method, utilizing statutory and conceptual approaches. The analysis is conducted through a systematic review of primary, secondary, and tertiary legal materials relevant to restorative justice and criminal case resolution. Results. The findings indicate that peace-based settlement mechanisms in criminal cases have gained formal recognition through various policies and regulatory instruments that support the application of restorative justice. Nevertheless, their implementation continues to face several obstacles, including the absence of comprehensive and unified regulation, inconsistencies in application among law enforcement authorities, and the risk of unequal bargaining positions between offenders and victims during the reconciliation process. Conclusions. The study concludes that the settlement of criminal cases through peace agreements has the potential to promote a more recovery-oriented form of justice. However, its effective application requires stronger regulatory frameworks, consistent implementation practices, and adequate oversight mechanisms to ensure alignment with the principles of legal certainty and the protection of human rights.